Koreografi Tari Emun Berereng Karya Mukhlis Gayo di Aceh Tengah - Dedek Dedek (Universitas Negeri Medan, 2016)
The theory used in this research is the theory Koreeografi of Sudarsono. When the study to discuss Emun Berereng dance performed during 2 months, ie from the beginning of October 2015 to December 2015. The study Desa Blang Kolak II District Bebesen Central Aceh district. The population is a resource, artists, traditional leaders and dancers who know about dance Gayo especially dance Emun Berereng in Central Aceh, the sample in this study were numbered four persons namely speakers, traditional leaders, artists and dancers dance Emun Berereng in Aceh Central. Data collection techniques include literature study, observation, Interview, and documentation, which is then analyzed by qualitative descriptive method. Based on research done that dance Emun Berereng have a soft form of motion, the design contained on the dance floor Emun berereng is catastrophically, split, alternately and interchangeably. Top design contained in this dance is the design on a flat, contrast, vertical, medium, low, and high pending. Dance wear Emun Berereng external musical accompaniment accompaniment yaiu born noise generated by devices outside the human body like a drum, flute, harp and other musical instruments. The themes contained in this dance is how the relationship young people gayo in mengespresikan feelings of love towards people in sukain in ancient times, Clothing used in dance Berereng Emun this is a long-sleeved shirt filigree headdress that had been in kreasikan (headscarf). Property used in dance Emun Berereng is scarves.